Healthcare workers safety: a cohort study using healthcare utilisation databases on vaccination and vaccine timeliness impact against SARS-CoV-2 infection - Edlira Skrami; Andrea Faragalli; Marica Iommi; Marco Morbidoni; Cristina Mancini; Antonella Guidi; Annalisa Cardone; Marco Pompili; Pietro Serafini; Remo Appignanesi; Luigi Ferrante; Flavia Carle (Scientific Reports)
Abstract Healthcare Workers (HCWs) are at ongoing risk of SARS-CoV-2 infection, potentially contributing to its transmission. This study assessed full vaccination and vaccination timeliness impact on SARS-CoV-2 infections among HCWs in Italy’s Marche Region, using Healthcare Utilization Databases. We evaluated vaccination coverage and its associated factors. The cohort comprised 21,118 HCWs aged 18–70 from the region’s five Local Health Authorities (LHA), enrolled between February 2020 - May 2021. Factors associated with full vaccination were assessed using multiple logistic regression. The impact of vaccination status, time to vaccination, occupational role, age, gender, and health status on infection risk was analysed with a multiple Cox regression model, adjusting for vaccination coverage velocity, swabbing probability, and monthly intensive care unit admissions rate in each LHA. Of the cohort, 81.2% were fully vaccinated. Factors associated with full vaccination included age, role, LHA, prior infection, and health status. Vaccination reduced infection risk by 77% (95% CI: 70–82). Infection risk was higher among healthcare assistants, nurses/physiotherapists/technicians compared to physicians, among male HCWs, and it decreased as vaccination timeliness increased. Vaccination timeliness is crucial for reducing SARS-CoV-2 infection risk among HCWs, regardless of their characteristics. This underscores the importance of efficiently organizing vaccination administration across different territories and for all HCW categories.